PENGARUH KUALITAS PELAYANAN CUSTOMER SERVICE TERHADAP KEPUASAN PELANGGAN GRAPARI TELKOMSEL MADIUN - Mursyid, Mursyid; Purwanta, Purwanta; Suliantoro, Suliantoro (LPPM Akademi Manajemen Administrasi Yogyakarta, 2023)
One of the key success factors for the provision of cellular services in this competitive era is the ability of an operating network to provide customer service to the public. The desire to successfully solve problems while satisfying customers is part of the work culture of Telkomsel employees. Caring for consumers is important. The purpose of conducting this research is to determine the effect of service quality which consists of dimensions of tangible, reliability, responsiveness, assurance and empathy partially and simultaneously on customer satisfaction at Grapari Telkomsel Madiun. Based on the results of the discussion, it can be concluded that service quality which consists of tangible, reliability, responsiveness, assurance and empathy dimensions partially and simultaneously has a significant effect on customer satisfaction at Grapari Telkomsel Madiun.